2022
DOI: 10.3390/jmse10020141
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Contact Pressure Calculation Method for the Misaligned Elastomeric Journal Bearing

Abstract: The pressure distribution of a misaligned elastomeric journal bearing is crucial for analyzing the uneven excessive wearing of the propulsion shaft bearing. However, analysis of the misaligned bearing is usually mainly based on the finite element method (FEM), which lacks a convenient and effective calculation method. This paper uses the influence coefficient factors (ICs) method to analyze the contact pressure of the misaligned bearing. First, the elastic displacement of the cylindrical shell subjected to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In that particular case study of the shafting system of an 82000 DWT bulk carrier, the initial alignment of the vessel was compared against the performance corresponding to different bearing offset combinations. Similar studies have been recently reported by other researchers especially focusing in the important effect of hull structural deformations in regard to shaft alignment [12][13][14].…”
Section: Introduction and Literature Trendssupporting
confidence: 88%
“…In that particular case study of the shafting system of an 82000 DWT bulk carrier, the initial alignment of the vessel was compared against the performance corresponding to different bearing offset combinations. Similar studies have been recently reported by other researchers especially focusing in the important effect of hull structural deformations in regard to shaft alignment [12][13][14].…”
Section: Introduction and Literature Trendssupporting
confidence: 88%
“…The study found that hull deformation is a significant factor in shaft alignment and that the matrix displacement method is an effective tool for calculating hull deformation. This research provides valuable insights into the importance of considering hull deformation when aligning shafts and highlights the usefulness of the matrix displacement method in this regard [17].…”
Section: Introductionmentioning
confidence: 90%
“…The study also shows the substantial impact of hull deflection on shaft alignment in medium-sized ships [16]. Zhou et al (2023) investigated the effects of hull structural deformation on shaft alignment. The study divided hull deformation into global and local deformations and simplified them into two models: single-span and grillage beam.…”
Section: Introductionmentioning
confidence: 99%
“…[22] and Ref. [24], respectively. In the third stage, there are two pressure cases corresponding to the initial start/stop and continuous operation of the shaft system, namely static contact pressure and dynamic hydrodynamic pressure.…”
Section: Case Study Of the Effect Of Hull Deformation On Shaft Alignmentmentioning
confidence: 99%
“…Analysis of the bearing failure form demonstrates that side abrasion with an angle between the shaft and the bearing also occurs frequently. An increasing amount of research [24][25][26] has discovered that the relative angle influences the load area and pressure distribution of a single bearing significantly. As the scale of the bearing increases, it becomes inappropriate to analyze the bearing's operating condition by simplifying the bearing to a simple point and ignoring the relative position relationship between the shaft and the bearing.…”
Section: Introductionmentioning
confidence: 99%